As crises da educação e formação de adultos em Portugal - Antónia Távora; Henrique Vaz; Joaquim Coimbra (Escola Superior de Educação de Paula Frassinetti, 2012)
This article is based on the assumptions of a conception of Lifelong Learning (LLL) and Adult Education and Training (AET) under a political vision, developing a contextualized analysis of their goals that arise, in order to understand and identify their embodiments in Portugal and the different government priorities behind the initial formulations of such educational policies. In the current context of crisis, where the unstable economic growth has contributed decisively to the rise in unemployment and precarious work, the AET's image in the political debate has departed from its original humanistic root towards a compensatory measure, strictly regarding programs of educational and/or professional qualifications.